Herb-Drug Interaction Evaluation on Concomitant Administration of IME-9 and Gliclazide in Preclinical Diabetic Rats - Thikekar, Archana Kondibhau; Thomas, Asha Byju; Chitlange, Sohan Satyanarayan; Sanap, Avinash Purushottam; Bhonde, Ramesh Ramchandran; Chaudhari, Somdatta Yashwant (Indian Journal of Pharmaceutical Education and Research)
Background: Diabetes mellitus is the third most prevalent cause of mortality and morbidity globally. Several complementary or alternative therapies currently used to treat diabetes mellitus. IME-9 is a polyherbal preparation used to treat diabetes and contains numerous phytoconstituents that can alter the cytochrome enzymes, mainly CYP2C8, 2B6, 2D6, 1A2, 2C9, 2C19, and 3A4. Gliclazide is a commonly prescribed antidiabetic drug metabolized primarily by the CYP2C9 and CYP2C19 enzymes. Thereby, it is postulated that the concomitant administration of IME-9 with Gliclazide therapy in diabetic patients may lead to HDI (Herb-Drug Interaction). Materials and Methods: In the Pharmacokinetic (PK) and Pharmacodynamic (PD) Herb-Drug Interaction (HDI) studies, GL was given to rats orally at 8.22 mg/kg, followed by administration of IME-9 at a dose of 132.24 mg/kg for 21 days. On the 1st day and after 21 days of the study period, in vivo PK/PD parameters were evaluated. In silico molecular docking studies were carried out (Autodock Vina1.2.3) to explore the binding affinity of the 46 major phytoconstituents present in IME 9 with the CYP2C9 and CYP2C19 enzymes. The toxicity was studied by MTT assay. Results: The PK analysis showed that co-administration of (IME-9+GL) for 21 days altered the PK parameters, increasing the Gliclazide (GL) bioavailability. This study throws light on the occurrence of hypoglycemia following the concomitant administration of (IME-9+GL) post 21 days in rats, leading to significant HDI, which may further lead to deleterious effects such as hypoglycemic coma. Furthermore, it was observed that the co-administration did not restore the body weight but restored the plasma TC and TG levels to normal. Histopathology studies revealed pathological alterations in the pancreas of diabetic control rats, while the treated rats (GL, IME-9) showed moderate degeneration with focal necrosis and atrophy in the islet of Langerhans. The in silico study confirms the critical involvement of the cytochrome enzymes in the observed HDI. Conclusion: This preclinical study can help to identify potential HDI and take the appropriate measures to improve clinical outcomes and reduce the associated adverse effects.
Keywords: Diabetes Mellitus; Gliclazide; HDI; IME-9; Pharmacodynamic; Pharmacokinetic.